Using Art as Therapy with a Child with Attention Deficit/Hyperactivity Disorder - Comorbid Intellectual Disability: A Case Study - Hina Ayaz, (Journal of Basic & Applied Sciences, 2018)
Objective: The aim of the present study is to highlight the significance of Art as therapy for the reduction of symptoms of Attention Deficit Hyper Activity Disorder. Place of Study: Karachi, Pakistan. Research Design: Case study. Sample and Method: This paper is based on a case of a 6 year and 5 months old girl with Attention Deficit Hyper Activity Disorder predominantly hyperactive-Impulsive type and Mild Intellectual disability diagnosed by Trained and qualified clinical psychologist At Institute of Clinical Psychology, University of Karachi. She was regular student of Special school, Karachi Pakistan. She was given 25 sessions of behavioral approach to art therapy. ADHD-T was administered (pre-post intervention) for measuring the intensity of symptoms Attention Deficit Hyper Activity Disorder and improvement in the developmental and artistic level of the child. Conclusions: The results revealed the effectiveness of art therapy in reduction of the symptoms of Attention Deficit/hyperactivity Disorder. The improvement is vivid in the graphic presentation of the art work. Limitations and implications were also discussed. Results: Results showed decrease in the intensity of the symptoms of Attention.